The association between breastfeeding technique and knowledge with exclusive breastfeeding - Lina Handayani; Yunengsih Yunengsih; Solikhah Solikhah; Azidanti Saufi (Faculty of Medicine, Universitas Islam Indonesia, 2016)
Background : Breastmilk is the ideal food for babies. There are various inhibiting factors for the formation of awareness of parents in providing exclusive breastfeeding for example ignorance from the mother about the importance of breastfeeding, how to breastfeed properly, and aggressive marketing launched by infant formula manufacturers. Objective : TThis study aimed to determine the association between knowledge and techniques of breastfeeding with exclusive breastfeeding in the area of Puskesmas Pengasih II, Kulonprogo. Methods : This research employed cross-sectional design. The population was all mothers with babies six to 12 months with total sample 142 mothers. The data was analyze using Chi-square test with alpha significance=5%. Results : This study found more subjects with a low level of knowledge (57%), the same goes with breastfeeding technique (52,1%). There was statistically significant association between knowledge with exclusive breastfeeding (p=0,006). There was a statistically significant association between breastfeeding technique with exclusive breastfeeding (p=0,002). Conclusion : There were relationships between knowledge (p = 0.006) and feeding techniques (p = 0.002) with exclusive breastfeeding.